The path of an Ecuadorian vegan young: The Conviction subjected to Reality - Menes Aguirre, Iván (El Outsider: Journal of International Relations and Political Science, 2025)
This essay traces the journey through which individuals, once omnivores, adopt veganism out of conviction. Using a focus group, it analyzes the steps involved in choosing this diet. In this regard, the article aims to understand how social interactions and contextual conditions influence the vegan trajectory. Employing a qualitative methodology, it reconstructs this personal process into a standardized one, highlighting shared experiences. The study seeks to explore areas often overlooked by the sociology of food, particularly concerning how individuals come to embrace veganism. To this end, it reviews relevant literature and presents this trajectory as comprising three stages: early veganism, the transition phase, and consolidation.
Keywords: Veganism; Sociology of food; Trajectory; Ecuadorian university students; Intrafamily relations; Socioeconomical conditions